The influence of toddler mothers class application on maternal behavior in complementary breastfeeding - Setiawati, Desy; Virgian, Kharisma; Suprida, Suprida (Science Midwifery, 2024)
An important period in a child's growth and development is the period under five years (toddlers), because this period is a period of basic growth that will affect and determine the child's subsequent development. During toddlerhood, children experience rapid growth and development and are often referred to as the golden period as well as the critical period. Health workers have a role in promoting knowledge about the health of toddlers to parents. The toddler mother class is a form of activity that provides knowledge to mothers about the health of their toddlers. This study analyzes the influence of android applications for mothers under five on maternal behavior in providing complementary foods for breast milk to toddlers 1-2 years old at the Palembang City Independent Practice Midwifery. The research method uses a Quasi experiment research design using a one-group pretest and posttest design approach. Based on the results of the statistical test using the McNemar statistical test, a ρ value of 0.000 (α<0.005) was obtained, a meaningful difference was obtained between the behavior of mothers before and after using the Mother of Toddler Class application through the android application. This research is expected to be useful for mothers of toddlers and can be used as input material for midwives as an alternative method of implementing classes for mothers under five years old.